Optimization method for foam metal electrode of hydrogen electrolysis cell

By optimizing the material and structure of the foam metal electrode, the problem of insufficient durability and electrocatalytic activity is solved, and more efficient hydrogen production and longer electrolytic cell operation are achieved, improving the overall performance and economy of the electrolytic cell.

CN119243209APending Publication Date: 2025-01-03NANTIANSHUJIN (BEIJING) INFORMATION IND DEV CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411454743.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The durability and electrocatalytic activity of foam metal electrodes in existing alkaline electrolytic cells limit the long-term working efficiency and economicality of the electrolytic cells.

Method used

By selecting suitable foam metal materials (such as nickel-based, iron-based, copper-based), designing reasonable pore structures, and applying high-efficiency electrocatalysts and enhancing corrosion-resistant layers on the surface, optimizing electrode materials and structures, and adjusting electrolytic cell operating parameters by selecting suitable foam metal materials (such as nickel-based, iron-based, copper-based), and applying high-efficiency electrocatalysts to the surface and enhancing corrosion-resistant layers, optimizing electrode materials and structures, and adjusting electrolytic cell operating parameters. To improve electrode activity and corrosion resistance.

Benefits of technology

It significantly improves the electrocatalytic activity and corrosion resistance of the electrode, improves the hydrogen production efficiency and the long-term stability and economicality of the electrolytic cell.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243209A_ABST
    Figure CN119243209A_ABST
Patent Text Reader

Abstract

The invention provides a method for optimizing a foam metal electrode of a hydrogen electrolysis cell, and belongs to the technical field of electrochemistry, the method comprises the following steps: material selection and structural design: task definition: selecting a proper foam metal material, such as nickel-based, iron-based or copper-based foam metal, according to the requirement of hydrogen production by electrolysis of water, and selecting a proper foam metal material, such as nickel-based, iron-based or copper-based foam metal, according to the requirement of hydrogen production by electrolysis of water; the materials need to have good conductivity and corrosion resistance; structural optimization: the pore structure of the foam metal electrode is designed, and an efficient electrocatalyst (such as platinum and iridium oxide) is loaded on the surface of the foam metal by adopting an electrodeposition, impregnation or chemical vapor deposition technology, so that the electrocatalytic activity of the electrode is remarkably improved, the overpotential of a hydrogen evolution reaction is reduced, the electrochemical reaction rate is further increased, the hydrogen production efficiency is improved, and the hydrogen production efficiency is improved. The catalyst deposition method ensures the uniformity and controllability of the catalyst layer, so that the electrochemical reaction is more efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a method for optimizing foam metal in a hydrogen electrolyzer. Background Art

[0002] Problems faced in existing water electrolysis hydrogen production technologies, especially in the application scenarios of alkaline electrolyzers using foamed metals as electrode materials. The prior art has recognized that by using foamed metals as electrode materials, the specific surface area of ​​the electrodes can be significantly increased, thereby improving the electrolysis efficiency and hydrogen production rate. However, the shortcomings may include the durability and electrocatalytic activity of the foamed metal electrodes in actual operation, which may limit the overall performance and economy of the electrolyzer.

[0003] Specifically, although the existing alkaline electrolyzer technology is relatively mature, there are still challenges in the selection and optimization of electrode materials, the design of pore structures, and surface modification. For example, although nickel-based foam metals are preferred due to their high corrosion resistance and mechanical strength, the cost advantage of iron-based and copper-based foam metals needs to be compensated by more sophisticated surface treatment to make up for their lack of corrosion resistance. In addition, how to design a reasonable pore structure to balance the fluid dynamics and electrochemical active area, and how to effectively coat the surface of the foam metal with high-efficiency electrocatalysts and enhance its corrosion resistance are key technical issues to be solved.

[0004] In order to solve the above problems, the present invention provides a method for optimizing foam metal in a hydrogen electrolyzer. Summary of the invention

[0005] The purpose of the present invention is to provide a method for optimizing foam metal electrodes for hydrogen electrolyzers, aiming to solve the problems in the prior art that the durability of foam metal electrodes in actual operation is insufficient, which limits the long-term working efficiency and economy of the electrolyzer, and the electrocatalytic activity of the electrode material is insufficient to support efficient electrolysis reactions, affecting the hydrogen production rate and overall efficiency.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for optimizing the foam metal of a hydrogen electrolyzer, comprising the following steps:

[0008] Step 1: Material selection and structural design:

[0009] The task is clear: according to the needs of water electrolysis to produce hydrogen, select suitable foam metal materials, such as nickel-based, iron-based or copper-based foam metals. These materials must have good conductivity and corrosion resistance;

[0010] Structural optimization: Design the pore structure of the metal foam electrode, including pore size, shape (e.g., circular, hexagonal), and porosity, to maximize the specific surface area, ensure that the electrolyte can fully penetrate and promote effective gas emission;

[0011] Step 2: Surface modification:

[0012] Catalyst deposition: using methods such as electrodeposition, impregnation or chemical vapor deposition to coat or load high-efficiency electrocatalysts, such as platinum and iridium oxide, on the surface of the foam metal to improve the electrocatalytic activity;

[0013] Enhanced corrosion resistance: The corrosion resistance of the foam metal surface is enhanced through anodizing, coating treatment and other means to ensure long-term operation stability;

[0014] Step 3: Integration and preliminary testing:

[0015] Assembling the electrolytic cell: installing the optimized metal foam electrode in the electrolytic cell, and configuring appropriate electrolyte (such as alkaline or acidic solution) and auxiliary electrode;

[0016] Initial performance test: operate the electrolyzer under controlled conditions, record key parameters such as hydrogen production rate and energy consumption, and preliminarily evaluate the optimization effect;

[0017] Step 4: Parameter tuning and efficiency evaluation:

[0018] Parameter optimization: Based on the preliminary test results, the operating parameters of the electrolyzer, such as current density, electrolyte concentration and temperature, are adjusted to find the best working conditions;

[0019] In-depth testing: Long-term operation tests are carried out under optimized conditions to evaluate the electrolysis efficiency, stability and economic indicators in detail.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. In this scheme, by using electrodeposition, impregnation or chemical vapor deposition technology to load high-efficiency electrocatalysts (such as platinum and iridium oxide) on the surface of the foam metal, the electrocatalytic activity of the electrode is significantly improved, the overpotential of the hydrogen evolution reaction is reduced, and the electrochemical reaction rate is accelerated, thereby improving the hydrogen production efficiency. This catalyst deposition method ensures the uniformity and controllability of the catalyst layer, making the electrochemical reaction more efficient.

[0022] 2. In this scheme, after the foam metal electrode is anodized and coated, a dense oxide layer and an additional protective barrier are formed on its surface, which effectively resists the erosion of corrosive media, especially for iron-based and copper-based foam metals with relatively weak corrosion resistance. These treatment methods greatly enhance the corrosion resistance and long-term operation stability of the electrode, which not only extends the service life of the electrolyzer, but also ensures the continuity and reliability of the hydrogen production process.

[0023] 3. In this scheme, the pore structure of the foam metal electrode, including pore size, shape and porosity, is carefully designed to maximize the specific surface area of ​​the electrode, while ensuring good permeability of the electrolyte and effective discharge of the gas, promoting the balance between fluid dynamics and electrochemical active area. In addition, the optimal working conditions are found by finely adjusting the operating parameters of the electrolytic cell (such as current density, electrolyte concentration and temperature), which significantly improves the electrolysis efficiency and the economy of the system. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0025] Figure 1 The present invention is a flow distribution block diagram of a method for optimizing the foam metal pole of a hydrogen electrolyzer. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Example 1

[0028] See also Figure 1 , the present invention provides the following technical solutions:

[0029] A method for optimizing the foam metal of a hydrogen electrolyzer, comprising the following steps:

[0030] Step 1: Material selection and structural design:

[0031] The task is clear: according to the needs of water electrolysis to produce hydrogen, select suitable foam metal materials, such as nickel-based, iron-based or copper-based foam metals. These materials must have good conductivity and corrosion resistance;

[0032] Structural optimization: Design the pore structure of the metal foam electrode, including pore size, shape (e.g., circular, hexagonal), and porosity, to maximize the specific surface area, ensure that the electrolyte can fully penetrate and promote effective gas emission;

[0033] Step 2: Surface modification:

[0034] Catalyst deposition: using methods such as electrodeposition, impregnation or chemical vapor deposition to coat or load high-efficiency electrocatalysts, such as platinum and iridium oxide, on the surface of the foam metal to improve the electrocatalytic activity;

[0035] Enhanced corrosion resistance: The corrosion resistance of the foam metal surface is enhanced through anodizing, coating treatment and other means to ensure long-term operation stability;

[0036] Step 3: Integration and preliminary testing:

[0037] Assembling the electrolytic cell: installing the optimized metal foam electrode in the electrolytic cell, and configuring appropriate electrolyte (such as alkaline or acidic solution) and auxiliary electrode;

[0038] Initial performance test: operate the electrolyzer under controlled conditions, record key parameters such as hydrogen production rate and energy consumption, and preliminarily evaluate the optimization effect;

[0039] Step 4: Parameter tuning and efficiency evaluation:

[0040] Parameter optimization: Based on the preliminary test results, the operating parameters of the electrolyzer, such as current density, electrolyte concentration and temperature, are adjusted to find the best working conditions;

[0041] In-depth testing: Long-term operation tests are carried out under optimized conditions to evaluate the electrolysis efficiency, stability and economic indicators in detail.

[0042] In a specific embodiment of the present invention,

[0043] Step 1: Material selection and structural design:

[0044] 11. Material selection:

[0045] Nickel-based, iron-based, and copper-based foam metals: These materials were selected as candidates because of their excellent electrical conductivity, which is essential for electrochemical reactions. Among them, nickel-based foam metals have performed well in many studies due to their good corrosion resistance and high mechanical strength, especially for alkaline electrolyte environments. Although iron-based and copper-based materials have lower costs, they may not be as corrosion-resistant as nickel-based materials, so more detailed surface treatment is required in specific applications to improve durability.

[0046] 12. Structural design:

[0047] Pore ​​structure optimization: The pore structure of metal foam is the key to its efficient operation. The pore size (usually in the range of tens to hundreds of microns) must be considered during design to balance the fluid dynamics and electrochemical active area. The pore shape (such as circular and hexagonal) affects the flow path of the electrolyte and the efficiency of bubble emission. The hexagonal structure often provides better structural stability and higher specific surface area. The optimization of porosity (i.e., the proportion of pore volume to total volume) aims to maximize the contact area between the electrolyte and the electrode while ensuring sufficient mechanical strength.

[0048] Step 2: Surface modification:

[0049] 21. Catalyst deposition:

[0050] High-efficiency electrocatalysts: Platinum and iridium oxides are commonly used high-efficiency electrocatalysts that can significantly reduce the overpotential of the hydrogen evolution reaction and increase the electrochemical reaction rate. Electrodeposition directly forms a uniform catalytic layer on the surface of the metal foam, while impregnation or chemical vapor deposition can more accurately control the loading and distribution of the catalyst, further improving the catalytic efficiency.

[0051] 22. Enhanced corrosion resistance:

[0052] Surface treatment technology: Anodizing can form a dense oxide layer on the surface of the metal foam, effectively blocking the erosion of corrosive media. Coating treatment (such as the use of polymer or ceramic coating) provides an additional protective barrier, especially for iron-based and copper-based metal foams with relatively weak corrosion resistance, which is a key measure to improve long-term stability.

[0053] Step 3: Integration and preliminary testing:

[0054] 31. Assemble the electrolytic cell:

[0055] System integration: Install the optimized metal foam electrode into the electrolyzer as cathode or anode (depending on the specific electrolysis process), ensuring compatibility and coordination with other components (such as diaphragm, electrolyte circulation system), and appropriate spacing between electrodes to optimize current density distribution;

[0056] 32. Initial performance test:

[0057] Evaluation indicators: By controlling experimental conditions (such as current density, electrolyte concentration, temperature, etc.), monitoring hydrogen production rate, energy conversion efficiency (measured in hydrogen production per kilowatt-hour of electricity), and long-term operation stability, these data not only verify the effectiveness of optimization measures, but also provide an empirical basis for subsequent further improvements;

[0058] Step 4: Parameter tuning and efficiency evaluation:

[0059] 41. Parameter optimization:

[0060] Current density adjustment: Current density directly affects the hydrogen production rate and energy consumption. By gradually adjusting and testing different current density values, we can find the best point that does not cause a sharp increase in overpotential while maintaining a high hydrogen production efficiency. Too high current density may cause local overheating and decreased catalyst stability, while too low current density will result in low efficiency.

[0061] 42. Electrolyte concentration control: The electrolyte (such as the concentration of KOH solution) has a significant effect on conductivity and reaction kinetics. Properly increasing the concentration can improve conductivity and accelerate ion transport. However, too high a concentration will increase the viscosity of the electrolyte and hinder the diffusion process. The optimal concentration range is determined through experiments to balance hydrogen production efficiency and energy consumption.

[0062] Temperature management: Temperature has a significant impact on the electrolysis reaction rate. Generally speaking, moderately increasing the operating temperature can speed up the reaction, but it also increases energy consumption. It is necessary to explore the optimal temperature range under the premise of ensuring equipment safety and material stability;

[0063] 43. In-depth testing;

[0064] Electrolysis efficiency evaluation: Under the optimal operating parameters found, long-term continuous operation tests are carried out to continuously monitor the hydrogen production rate, power consumption, etc., and calculate the electrolysis efficiency (i.e., the ratio of each unit of electrical energy converted into hydrogen energy). High electrolysis efficiency means lower energy costs and higher economic feasibility;

[0065] 44. Stability assessment: Long-term operation tests not only focus on the sustainability of hydrogen production efficiency, but also observe the physical morphology changes of the foam metal electrode, catalyst stability, and the overall durability of the electrolyzer to ensure reliability and life in actual applications.

[0066] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for optimizing the metal foam of a hydrogen electrolyzer, characterized in that: It includes the following steps: Step 1: Material selection and structural design: The task is clear: according to the needs of water electrolysis to produce hydrogen, select suitable foam metal materials, such as nickel-based, iron-based or copper-based foam metals. These materials must have good conductivity and corrosion resistance; Structural optimization: Design the pore structure of the metal foam electrode, including pore size, shape (e.g., circular, hexagonal), and porosity, to maximize the specific surface area, ensure that the electrolyte can fully penetrate and promote effective gas emission; Step 2: Surface modification: Catalyst deposition: using methods such as electrodeposition, impregnation or chemical vapor deposition to coat or load high-efficiency electrocatalysts, such as platinum and iridium oxide, on the surface of the foam metal to improve the electrocatalytic activity; Enhanced corrosion resistance: The corrosion resistance of the foam metal surface is enhanced through anodizing, coating treatment and other means to ensure long-term operation stability; Step 3: Integration and preliminary testing: Assembling the electrolytic cell: installing the optimized metal foam electrode in the electrolytic cell, and configuring appropriate electrolyte (such as alkaline or acidic solution) and auxiliary electrode; Initial performance test: operate the electrolyzer under controlled conditions, record key parameters such as hydrogen production rate and energy consumption, and preliminarily evaluate the optimization effect; Step 4: Parameter tuning and efficiency evaluation: Parameter optimization: Based on the preliminary test results, the operating parameters of the electrolyzer, such as current density, electrolyte concentration and temperature, are adjusted to find the best working conditions; In-depth testing: Long-term operation tests are carried out under optimized conditions to evaluate the electrolysis efficiency, stability and economic indicators in detail.